Estrangeirismo ou Português? Eis a questão: uma proposta para adequação linguística - Araújo, Rosimeire viviane de Oliveira Araújo (2023)
This research presents the presence of foreign words in the Portuguese language, the "estrangeirismo", which is the target of negative criticism by purist groups. Therefore, there is no effective approach on this subject in the teaching of Portuguese. Therefore, this paper aims to elaborate an intervention proposal to teach lexical in the perspective of linguistic variation, including foreign lexical items, to contribute to the expansion of the lexical repertoire, linguistic adequacy, and communicative competence of students. To this end, we carried out a bibliographic and documental study, especially in works related to linguistic variation, Sociolinguistics, and Lexicology. Thus, as a theoretical basis, this research was based on Alves (1990; 1984), Antunes (2012), Bagno (2001), Barbosa (1978, 1979; 1981), Biderman (1978; 1984; 2001), Bortoni-Ricardo (2005), Cristianini (2007), among others. As for the methodological aspects, we adopted the action research, having as participants a group of 35 7th grade students from a public school in Goiânia-GO. The intervention proposal was applied by means of an initial survey questionnaire to determine prior knowledge and, subsequently, five pedagogical workshops distributed in 24 hours/class. For the constitution of the corpus and data analysis, we compiled the results of the application of the intervention proposal, along with a report of the observations of researcher-teacher. The results were shown by means of charts, graphs, and critical-reflexive analysis, in a quantitative-qualitative approach. We believe that the objectives were achieved, since the intervention proposal contributes to lexical teaching, allows the inclusion of foreign words in the approach to linguistic variation and provides an opportunity to expand the lexical repertoire, linguistic adequacy, and communicative competence of the students. As a final product, we produced an Activity Notebook to be available to Portuguese Language teachers in Basic Education.